Awareness on The Impact of Religious Gathering on The Spread of Covid-19 - A Cross Sectional Survey - RAM, ASHWIN JAIKUMAR; ANJALI, A.K.; K. ANJANEYULU (The journal of contemporary issues in business and government, 2020)
COVID -19 is a harmful virus. It is caused by SARS-CoV2 that is Severe Acute Respiratory Syndrome. Coronaviridae is the family to which it belongs. The study report says that SARS will also lead to complications such as MERS that is middle east respiratory syndrome. Worship places should be cleaned frequently if people are allowed to enter the holy places during the pandemic situation. The aim of the study is to find out whether COVID-19 patients attending religious gatherings lead to communal riots or not. A survey- based study consisting of self structured questionnaires was prepared and circulated through social networking. The results were collected and then analysed through SPSS software. Descriptive statistical analysis was carried out and chi square test was used and p value was calculated. From the results obtained, we came to know that COVID-19 patients attending religious gatherings will pave the mark for the communal riots and people should avoid contact with the devotional objects and avoid contact with people attending religious faith services. Therefore we conclude that COVID 19 patients attending religious gatherings will be marked by the communal riots.